The Impact of Mobile Banking (M-Banking) Services on Customer Satisfaction of the State Savings Bank (BTN) - Saptani Rahayu; Indriyana Widyastuti (STIE AUB Surakarta, 2022)
The goal of this study is to determine and demonstrate the effect of mobile banking services on customer satisfaction. Quantitative method used in this research. Primitive data gathered by distributing questionnaires online to respondents who use BTN mobile banking services in Surakarta is used as a data source in this study. There are 100 respondents in the total sample. In this study, linear regression analysis was used to test the classic hypotheses and assumptions. The results showed that system information security had a positive and significant effect on customer satisfaction, ease of use of services had a positive and significant effect on customer satisfaction, and bank reliability had a significant positive effect on customer satisfaction. The results of the F test show that system security, service ease of use and bank reliability have a significant effect on customer satisfaction. The results of the coefficient of determination (R2) show that the influence of this study is 62.5%, the remaining 37.5% can be explained by other factors not examined in this study.